2012
DOI: 10.1111/cpr.12001
|View full text |Cite
|
Sign up to set email alerts
|

Elastic three‐dimensional poly (ε‐caprolactone) nanofibre scaffold enhances migration, proliferation and osteogenic differentiation of mesenchymal stem cells

Abstract: We draw the conclusion that all positive effects observed using the 3D PCL nanofibre scaffold are related to the larger fibre surface area available to the cells. Thus, the proposed 3D structure of the nanofibre layer will find a wide array of applications in tissue engineering and regenerative medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 49 publications
(54 reference statements)
3
74
0
Order By: Relevance
“…Most tissue engineering applications demand 3D-structured scaffolds with open pores to enable cell infiltration. Different strategies such as special collectors 17 and salt leaching 18 were used to enhance the pore size and thickness of nanofibrous layers. Currently, alternative methods to prepare nano-and microfibers, such as melt-blown or centrifugal spinning, are being tested for tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…Most tissue engineering applications demand 3D-structured scaffolds with open pores to enable cell infiltration. Different strategies such as special collectors 17 and salt leaching 18 were used to enhance the pore size and thickness of nanofibrous layers. Currently, alternative methods to prepare nano-and microfibers, such as melt-blown or centrifugal spinning, are being tested for tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…Jakubova et al 21 Chen et al 26 and Rampichová et al 28 proved that PCL nanofibers support the attachment and growth of fibroblasts, chondrocytes, and mesenchymal stem cells. In addition, PCL nanofibers as novel absorbable scaffolds for hernia-repair application were biomechanically tested by Ebersole et al 34 The authors have shown that electrospun PCL scaffolds retain suture material and possess tensile strength appropriate for hernia repair, and thus have the potential to be a novel class of hernia-repair materials.…”
Section: Discussionmentioning
confidence: 99%
“…PCL has been shown to support the attachment and growth of chondrocytes, 21 osteoblasts, 22,23 smooth-muscle cells (SMCs), 24 fibroblasts, 22,25,26 myoblasts, 27 and mesenchymal stem cells. 28 In a recent study, we developed a composite nanofiber-PP mesh. The purpose of this study was to evaluate the potential benefit of the PCL nanofiber mesh in vitro and in vivo in hernia surgery.…”
mentioning
confidence: 99%
“…22 PCL has frequently been chosen for electrospinning, because it is a US Food and Drug Administration (FDA)-approved material and has been shown to support the attachment and growth of chondrocytes, 23 osteoblasts, 24,25 smooth muscle cells, 26 fibroblasts, 24,[27][28][29] myoblasts, 30 and mesenchymal stem cells (MSCs). 31 PCL appears to be a suitable material for scaffold preparation for reparative surgery. It has been used in wound healing, 32 and could be used in combination with a surgical mesh in ventral hernia regeneration.…”
mentioning
confidence: 99%
“…Various studies have proved that nanofibers -namely, PCL nanofibers -support the adhesion, growth, and proliferation of fibroblasts, chondrocytes, and MSCs. 23,28,31 Moreover, PCL nanofibers possess suture retention and tensile strength appropriate for most hernia repairs. The studies of Ebersole et al 12 and Deeken et al 48 showed that electrospun scaffolds having mechanical properties within the predefined range may be suitable for further evaluation in preclinical trials.…”
mentioning
confidence: 99%